“Desde a aurora ao entardecer”: uma análise da dinâmica urbana no município de Vargem Grande – MA (1980-2010) - LAGO, Eva Rosa do (2021)
This research seeks to analyze the urban dynamics in the city of Vargem Grande - MA from the growth of neighborhoods in the period from 1980 to 2010, having as a central phenomenon the mobility of populations residing in the countryside to the city. In this sense, it discusses the specificities of the city's space and the characteristics that made it an attractive pole for such populations. It also analyzes the experiences of the subjects who experienced this process, seeking to characterize their lives based on their reports, as well as the individual and collective imagination that projects the city space as a solution to all the difficulties encountered in their former place of origin, exploring the elaboration of social relationship networks through the experiences shared by family, friends and neighbors about the advantages found within the city. Among the factors that implied the mobility of these populations, as well as the consequent process of expansion of the city, pointed out by the interviewees were: the constant conflict with landowners in the countryside, focusing on the expulsion of residents and the perception of the city as a locus of access to goods and services, such as work, health, education. These aspects of life in Vargem Grande in Maranhão are studied having as main sources the oral reports of subjects residing in the city coming from the countryside during this period, as well as IBGE data for the municipality, notes in a poem and a diary found within the scope of research. The study claims the perspective of a history seen from below, in which it situates common subjects in the city's history from a methodological approach to demographic history, connecting mainly to Oral History, which is taken as directive throughout the work. It also adopts micro-History and comparative history procedures in order to carry out an analysis in which the issues raised by the research in this small town in Maranhão can be presented as a relevant discussion for any other spaces as, through this, we can perceive nuances of so many other spaces and other temporalities. For this research, authors such as Pesavento, Harvey, Lefebvre and Ferreira were essential for the proposed discussion.